Implementation of Project Based Learning Model Based on Ethnoscience For Improving Learning Outcomes Biology - Rofifah, Lulu Rosyidah; Astuti, Dwi Setyo (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine the effectiveness of the ethnoscience-based Project Based Learning (PjBL) learning model in improving student learning outcomes in Biology subjects at the high school level. The background of this study is based on the demands of 21st-century education that emphasizes the mastery of critical thinking skills, collaboration, creativity, and communication (4C), as well as the need for contextual learning that is relevant to local culture. The method used is quantitative descriptive with a pretest-posttest control group design. The sample consisted of two experimental classes and one control class from grade X students of the Tahfidz Program at SMA ABBS Surakarta. Data were collected through cognitive ability tests and analyzed using N-Gain scores and t-tests. The results showed that there was an increase in learning outcomes in the experimental group with an average N-Gain of 56.5507 % (moderate category), but the increase was not statistically significant compared to the control group. Nevertheless, the integration of ethnoscience in PjBL has been shown to have a positive impact on understanding scientific concepts and preserving local cultural values. Therefore, this model has the potential to be an innovative alternative in contextual and meaningful Biology learning.